UV-A Sensor Based on 6H-SiC Schottky Photodiode - Antonella Sciuto; Massimo Cataldo Mazzillo; Salvatore Di Franco; Giovanni Mannino; Paolo Badala; Lucio Renna; Corrado Caruso (IEEE Photonics Journal)
In this paper, we propose a UV-A sensor based on a 6H-SiC Schottky photodiode with a thin Ni2Si front electrode and an integrated hydrogenated silicon nitride (SiN:H) dielectric filter. 6H-SiC prototypes were fabricated by using a manufacturing process to a large extent already implemented on 4H-SiC poly-type for the realization of a high signal-to-noise ratio ultraviolet (UV) sensor already commercialized. The results obtained on 6H-SiC prototypes show optimal electrical performance with dark current density lower than 0.2 nA/cm2 at room temperature and 10 V reverse bias. The use of 6H polytype allows shifting of the UV sensor response from 290 nm peak responsivity wavelength measured on standard 4H-SiC photodiodes to 360 nm wavelength in 6H-SiC prototypes with an integrated SiN:H filter exactly in the middle of the UV-A band (320–400 nm) with a simultaneous consistent reduction of the optical response in UV-C and UV-B regions below 320 nm wavelength.